Antimicrobial Resistance and Virulence Gene Profile of Clinical Staphylococcus aureus: A Multi-Center Study from Ethiopia - Ibrahim RA; Berhe N; Mekuria Z; Seyoum ET; Balada-Llasat JM; Abebe T; Mariam SH; Tsige E; Fentaw Dinku S; Wang SH (Infection and Drug Resistance, 2023)
Rajiha A Ibrahim,1– 3 Nega Berhe,1 Zelalem Mekuria,3,4 Eyasu T Seyoum,3 Joan-Miquel Balada-Llasat,3,5 Tamrat Abebe,6 Solomon H Mariam,1 Estifanos Tsige,2 Surafel Fentaw Dinku,2 Shu-Hua Wang3,7 1Aklilu Lemma Institute of Pathobiology, Addis Ababa University, Addis Ababa, Ethiopia; 2Bacterial, Parasitic and Zoonotic Research Directorate, Ethiopian Public Health Institute, Addis Ababa, Ethiopia; 3Global One Health Initiative (GOHi), The Ohio State University, Columbus, OH, USA; 4Veterinary Preventive Medicine, Colleges of Veterinary Medicine, The Ohio State University, Columbus, OH, USA; 5Department of Pathology, College of Medicine, The Ohio State University, Columbus, OH, USA; 6Department of Microbiology, Immunology, and Parasitology, Schools of Medicine, College of Health Sciences, Addis Ababa University, Addis Ababa, Ethiopia; 7Division of Infectious Diseases, Department of Internal Medicine, College of Medicine, The Ohio State University, Columbus, OH, USACorrespondence: Rajiha A Ibrahim, Bacterial, Parasitic and Zoonotic Research Directorate, Ethiopian Public Health Institute, PO Box: 1242, Addis Ababa, Ethiopia, Tel +251920602640, Email rajihabubeker@gmail.com; Ibrahim.258@osu.eduBackground: Staphylococcus aureus causes a wide range of infections from mild skin and soft tissue to severe life-threatening bacteremia. The pathogenicity of S. aureus infections is related to various bacterial surface components and extracellular proteins such as toxic-shock syndrome (TSS) toxin and Panton-Valentine leukocidin (PVL). In this study we determine the antimicrobial resistance of isolated strains and their virulence genes in Ethiopia.Methods: A total of 190 archived S. aureus isolates from four Ethiopia Antimicrobial Resistance (AMR) Surveillance sites were analyzed. The identification of S. aureus was done by matrix-assisted laser desorption/ionization-time of flight (MALDI-TOF Biotyper) and antimicrobial susceptibility test (AST) was done using VITEK® 2. Multiplex PCR was used to detect mecA, mecC, pvl and spa genes and super-antigens (sea, seb, sec, seh and sej staphylococcal enterotoxins).Results: A total of 172 isolates were confirmed as S. aureus, 9 (5.23%) were methicillin-resistant S. aureus (MRSA) and 163 (94.76%) were methicillin-susceptible S. aureus (MSSA). AST showed that 152 (88.4%) isolates were resistant to penicillin; 90 (52.32%) resistant to trimethoprim-sulfamethoxazole; and 45 (26.16%) resistant to tetracycline. A total of 66 (38.37%) isolates harbored at least one staphylococcal enterotoxin gene and 31 (46.96%) isolates had more than one. The most frequent enterotoxin gene encountered was seb 28 (16.28%). The TSST-1 gene was detected in 23 (13.37%). Presence of staphylococcal enterotoxin gene showed significant association with antibiotic resistance to cefoxitin, benzylpenicillin, oxacillin, erythromycin, clindamycin, tetracycline and SXT. The pvl gene was detected in 102 (59.3%) of isolates. Isolates from patients below 15 years of age showed significantly high numbers of pvl gene (P = 0.02). Presence of sej (P = 0.011) and TSST-1 (P < 0.001) genes were associated with the presence of pvl gene.Conclusion: In this study, isolates were highly resistant to oral antibiotics and the pvl, seb, sea and TSST-1 genes were prevalent.Keywords: MRSA, enterotoxin genes, Panton-Valentine leucocidin, PVL, Ethiopia